Building Bridges: Exploring the Nexus between Blind Recruiting and Organizational Performance in Oil and Gas Servicing Companies in South-South, Nigeria (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This study examined the relationship between blind recruiting and organizational performance in oil and gas servicing companies in Nigeria. The study adopted the cross-sectional research survey design. Primary data was generated through structured questionnaire. The population for the study comprises 6 of oil and gas servicing companies in south-south, Nigeria. All the oil and gas servicing companies’ 60 management staff` were sampled using census sampling techniques. The research instrument was validated by managers, vetting and approval while reliability of the instrument was achieved by the use of Cronbach Alpha coefficient which stood at .876. The hypotheses were tested using the Spearman’s Rank Order Correlation Statistics while the partial correlation was used to test the moderating effect. The test was carried out at a 0-05 significance level. The findings revealed that there is a significant relationship between blind recruiting and organizational performance of oil and gas servicing companies in south-south, Nigeria. The study concludes that blind recruiting positively enhances the organizational performance of oil and gas servicing companies in south-south, Nigeria. This implies that when blind recruiting is applied to personnel recruitment processes, there would be greater organizational performance. The study recommended among others that management of oil and gas servicing companies operating in South-South, Nigeria should invest in robust blind recruiting, placement and selection processes that carefully evaluate candidates for their skills, experience, and competencies to enhance organizational performance.